PENGUJIAN KEAMANAN APLIKASI BERBASIS WEB TERHADAP SERANGAN PARAMETER TAMPERING - Rakhmadi Rahman; Yonatan Rannu; Marwa Dinda Muchtar (CV. Denasya Smart Publisher, 2026)
The abstract contains a = Web application security is a critical aspect in ensuring the confidentiality and integrity of user data. One of the most common attack vectors is parameter tampering, which involves manipulating parameter values transmitted between the client and the server to alter application logic. This study aims to analyze the level of vulnerability of web applications to parameter tampering attacks and to identify the resulting security impacts. The research adopts a qualitative approach using a case study method through web application security testing based on black-box testing techniques. The testing process is conducted using tools such as Burp Suite and OWASP ZAP to observe application responses to parameter modifications. The results indicate that weaknesses in server-side parameter validation mechanisms still exist and may be exploited by attackers. Therefore, the implementation of strict server-side parameter validation and regular security testing is essential to enhance the overall security of web applications.